"Three‐in‐One:" A New 3D Hybrid Structure of Li3V2(PO4)3 @ Biomorphic Carbon for High‐Rate and Low‐Temperature Lithium Ion Batteries. Issue 22 (11th September 2017) - Cheng, Yi; Feng, Kai; Wang, Huaiqing; Zhang, Hongzhang; Li, Xianfeng; Zhang, Huamin
Abstract: Li3 V2 (PO4 )3 with high specific capacity and high operating potential has been considered as a promising cathode for the next generation lithium ion batteries (LIBs). But the low electronic conductivity restricts its practical applications. Here, a rational design of 3D hybrid structures of Li3 V2 (PO4 )3 @ biomorphic carbon is presented. The 3D hybrid structures built from 0D, 1D, and 2D composites are carbonized from biomorphic carbon, namely, "three‐in‐one." The synergistic effects of the carbon with different dimensions provide high electronic conductivity and good structural stability. In addition, abundant porous channels in the structure accelerate transfer of the Li + . This unique cathode material reaches the capacity retention up to 96% (relative to 1 C) when the rate increased to 50 C. When combines with Li4 Ti5 O12 to form a full battery, it delivers a capacity of 174 mAh g −1 at room temperature and retains 150 mAh g −1 when the temperature decreases to −40 °C. The excellent properties are attributed to the high electronic conductivity, fast ion transport channels, large electrode–electrolyte contact area, and robust structure stability of the 3D hybrid architecture. This work provides a new strategy for constructing 3D framework electrode materials for LIBs. Abstract : A 3D hybrid structure built by 0D, 1D, and 2D carbon is carbonized from the biomorphic carbon, namely "three‐in‐one." The synergistic effects of the carbon with different dimensions provide high electronic conductivity and good structural stability, which contribute to excellent rate performance and low‐temperature performance.